ERBEDAAN TINGKAT KECEMASAN MENGHADAPI PERSALINAN IBU PRIMIGRAVIDA SETELAH MENDENGARKAN AYAT SUCI AL-QUR’AN DI PUSKESMAS WILAYAH PURWOKERTO - Fauziah Hanum Nur Adriyani; Surtiningsih Surtiningsih; Mariah Ulfah (Viva Medika, 2014)
Pregnancy and childbirth on women is a fisiology process. However, the proses can cause anxiety on pregnant mother.Unstructured interviews to 3primigravida at Helath Centre Community Region of Purwokerto, as for 2 peopleto answer multigravida mother has not experienced anxiety in the face of labor.Series of research shows that listening therapy holy verses of Al-Qur’an canreduce the level of anxiety.The study aims to know the difference in the level ofanxiety facing labor primigravida trimester III therapy after listening to verses ofthe Al-Qur’an at Helath Centre Community Region of Purwokerto. This studyQuasi-experimental with one-group pre-posttest design. Sampel size is 40primigravida, sampling technique Quota Sampling. The study applied WilcoxonSigned Rank Test.Result of the study showed no difference in the level of anxietyin the face of labor primigravida after therapy holy verses of Al-Qur’an;statistically significant (p value = 0,000 < α = 0,05).The finding of this studyshows that no difference before and after listening therapy holy verses of AlQur’anto reduce anxiety in the primigravida trimester III in the face labor Helath Centre Community Region of Purwokerto. Key words:Al-Qur’an verses, anxiety, primigravida trimester III